Microvascular free flaps in the management of war wounds with tissue defects - Kozarski Jefta; Panajotović Ljubomir; Novaković Marijan (Vojnosanitetski Pregled)
Background. War wounds caused by modern infantry weapons or explosive devices are very often associated with the defects of soft and bone tissue. According to their structure, tissue defects can be simple or complex. In accordance with war surgical doctrine, at the Clinic for Plastic Surgery and Burns of the Military Medical Academy, free flaps were used in the treatment of 108 patients with large tissue defects. With the aim of closing war wounds, covering deep structures, or making the preconditions for reconstruction of deep structures, free flaps were applied in primary, delayed, or secondary term. The main criteria for using free flaps were general condition of the wounded, extent, location, and structure of tissue defects. The aim was also to point out the advantages and disadvantages of the application of free flaps in the treatment of war wounds. Methods. One hundred and eleven microvascular free flaps were applied, both simple and complex, for closing the war wounds with extensive tissue defects. The main criteria for the application of free flaps were: general condition of the wounded, size, localization, and structure of tissue defects. For the extensive defects of the tissue, as well as for severely contaminated wounds latissimus dorsi free flaps were used. For tissue defects of distal parts of the lower extremities, scapular free flaps were preferred. While using free tissue transfer for recompensation of bone defects, free vascularized fibular grafts were applied, and in skin and bone defects complex free osteoseptocutaneous fibular, free osteoseptocutaneous radial forearm, and free skin-bone scapular flaps were used. Results. After free flap transfer 16 (14,4%) revisions were performed, and after 8 unsuccessful revisions another free flaps were utilized in 3 (37,5%) patients, and cross leg flaps in 5 (62,5%) patients. Conclusion. The treatment of war wounds with large tissue defects by the application of free microvascular flaps provided shorter wound-closing period, earlier beginning of physical therapy, as well as the treatment of great number of patients with the extensive tissue defects in the conditions of massive influx of the wounded.